2002
DOI: 10.1034/j.1399-0039.2002.600205.x
|View full text |Cite
|
Sign up to set email alerts
|

HLA in coeliac disease families: A novel test of risk modification by the ‘other’ haplotype when at least one DQA1*05‐DQB1*02 haplotype is carried

Abstract: Predisposition to coeliac disease (CD) involves HLA genes. We investigated whether any haplotypes modify risk when carried trans to a known high-risk haplotype, DQA1*05-DQB1*02. Earlier attempts to rank levels of risk contributed by the 'other' haplotype were burdened by use of case-control populations; haplotype frequencies were estimated and homozygosity was only presumed. In contrast, exact haplotypes can be determined and allele transmission can be traced in families. A similar study in narcolepsy reported… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
37
0
2

Year Published

2003
2003
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(40 citation statements)
references
References 26 publications
1
37
0
2
Order By: Relevance
“…[12][13][14] Recently, a family-based study using phase-known haplotypes also demonstrated increased risk for these two genotypes. 11 A possible explanation for the increased risk may reside in the number of DQ molecules capable of gluten presentation that arise from each genotype. The homozygous DQA1*05-DQB1*02 genotype produces 100% DQ2 molecules.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[12][13][14] Recently, a family-based study using phase-known haplotypes also demonstrated increased risk for these two genotypes. 11 A possible explanation for the increased risk may reside in the number of DQ molecules capable of gluten presentation that arise from each genotype. The homozygous DQA1*05-DQB1*02 genotype produces 100% DQ2 molecules.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, the homozygous DQA1*05-DQB1*02/DQA1*05-DQB1*02 (DR3/3) and the heterozygous DQA1*05-DQB1*02/DQA1*0201-DQB1*02 (DR3/7) genotypes were shown to be associated with increased risk. [11][12][13][14] The extended HLA-DR3-DQ2 haplotype includes many other genes that play a role in the immune response and it cannot be excluded that another HLA gene also confers increased risk to coeliac disease. The HLA region is known to display extensive linkage disequilibrium (LD).…”
Section: Introductionmentioning
confidence: 99%
“…11,12 All affected family members strictly fulfilled the ESPGAN (European Society of Pediatric Gastroenterology and Nutrition) diagnostic criteria. 13 …”
Section: Subjectsmentioning
confidence: 99%
“…17 18 The data using direct DQ genotyping are limited to studies in European and North African countries. [19][20][21][22] There is also some evidence of a dosage effect of these genes: Studies in predominantly pediatric Norwegian and Sardinian populations suggested that those who are homozygous for DQB1*02 in the presence of DQA1*05 have a higher risk of developing CD and do so with greater severity. 23,24,21 A second study from Spain suggested that a double dose of DQB1* 02 was associated with earlier age of onset and shorter delay to diagnosis.…”
Section: Introductionmentioning
confidence: 99%